Genetic population structure of the pelagic mollusk Limacina helicina in the Kara Sea - Abyzova, Galina Anatolievna; Nikitin, Mikhail Aleksandrovich; Popova, Olga Vladimirovna; Pasternak, Anna Fedorovna (PeerJ, 2018)
Background Pelagic pteropods Limacina helicina are widespread and can play an important role in the food webs and in biosedimentation in Arctic and Subarctic ecosystems. Previous publications have shown differences in the genetic structure of populations of L. helicina from populations found in the Pacific Ocean and Svalbard area. Currently, there are no data on the genetic structure of L. helicina populations in the seas of the Siberian Arctic. We assessed the genetic structure of L. helicina from the Kara Sea populations and compared them with samples from around Svalbard and the North Pacific. Methods We examined genetic differences in L. helicina from three different locations in the Kara Sea via analysis of a fragment of the mitochondrial gene COI. We also compared a subset of samples with L. helicina from previous studies to find connections between populations from the Atlantic and Pacific Oceans. Results 65 individual L. helinica from the Kara Sea were sequenced to produce 19 different haplotypes. This is comparable with numbers of haplotypes found in Svalbard and Pacific samples (24 and 25, respectively). Haplotypes from different locations sampled around the Arctic and Subarctic were combined into two different groups: H1 and H2. The H2 includes sequences from the Kara Sea and Svalbard, was present only in the Atlantic sector of the Arctic. The other genetic group, H1, is widespread and found throughout all L. helicina populations. ϕ ST analyses also indicated significant genetic difference between the Atlantic and Pacific regions, but no differences between Svalbard and the Kara Sea. Discussion The obtained results support our hypothesis about genetic similarity of L. helicina populations from the Kara Sea and Svalbard: the majority of haplotypes belongs to the haplotype group H2, with the H1 group representing a minority of the haplotypes present. In contrast, in the Canadian Arctic and the Pacific Ocean only haplogroup H1 is found. The negative values of Fu’s Fs indicate directed selection or expansion of the population. The reason for this pattern could be an isolation of the Limacina helicina population during the Pleistocene glaciation and a subsequent rapid expansion of this species after the last glacial maximum.
Keywords: Arctic; Pteropods; Kara Sea; Limacina helicina; Glaciations; Genetic diversity